Comparison of Central Corneal Thickness Measured by Hand-Held and Desk-Mounted Ultrasound Pachymeters in Glaucoma Patients. (July 2015) - Salim, Sarwat; Du, Haiming; Wan, Jim
ABSTRACT Purpose: The purpose of this study was to compare the accuracy and reproducibility of central corneal thickness measured by hand-held and desk-mounted ultrasound pachymeter in glaucoma patients under treatment. Methods: Prospective study of 65 glaucoma patients. Central corneal thickness was measured by two ultrasound pachymeters: the hand-held, portable PachPen (Accutome, Lynwood, WA), and the desk-mounted PacScan 300 (Sonomed, Lake Success, NY). Results: The mean ± SD central corneal thickness was 526.5 ± 44.8 µm and 530.0 ± 44.7 µm for the hand-held and desk-mounted pachymeters, respectively (p = 0.15). Linear regression analysis revealed a slope of 0.97 with Pearson correlation coefficient of 0.96. Bland-Altman analysis showed a mean difference of measurements by both pachymeters of 3.22 µm with two standard deviations = 9.51. Both instruments showed high intraobserver correlation: 0.972 for the hand-held pachymeter and 0.993 for the desk-mounted pachymeter. Conclusion: Central corneal thickness measurements were comparable with the use of hand-held and desk-mounted ultrasound units in glaucoma patients with good intraobserver reproducibility.